Membrane computing : 18th International Conference, CMC 2017, Bradford, UK, July 25-28, 2017, revised selected papers /: 18th International Conference, CMC 2017, Bradford, UK, July 25-28, 2017, revised selected papers. (2018) - Unknown
No abstract available